Impact of Date-tempeh Biscuit on the Nutritional Status of Stunted and Wasted Toddlers - Fatmah (Pakistan Journal of Nutrition, 2018)
Background and Objective: The nutritional problems in stunted and wasted toddlers decrease cognitive development and child productivity. This study aimed to evaluate the effect of date-tempeh biscuit consumption on the change in nutritional status of stunted and wasted toddlers. Methodology: A quasi-experimental design was used in a study conducted on 70 toddlers who consumed 50 g of biscuits for 90 days. Weight and height measurement done at pre-post study and bi-weekly. Nutrition education undertaken by research team in collaboration with integrated service post for under-five children cadres bi-weekly. Results: The nutritional status of children under five was stunted (31.4%), wasted (24.3%), normal (24.3%) and stunted-wasted (20%). Mean height per age (H/A) of stunted toddlers was -3.2±1.2, weight per height (W/H) of wasted toddlers was -3.1±1.7 and H/A and W/H of stunted-wasted toddlers were 3.3 for each measure. Wasted toddlers had a mean weight change of 1.9 kg and the highest increase in mean height of wasted toddlers was 2.5 cm. Wasted toddlers had the highest percentage of date-tempeh biscuit consumption (29%). Adherence to the recommendations for date-tempeh biscuit consumption affected the nutritional status of children under five in all groups (p = 0.015). Carbohydrate intake difference was correlated positively with weight changes (r = 0.26, p = 0.03). There was a significant relationship between the difference in fat intake with final weight (r = 0.254, p = 0.034). Conclusion: Date-tempeh biscuits can increase weight and height in wasted, stunted and wasted-stunted toddlers during 3 months of intervention.